Pendidikan kepemimpinan sebagai sarana pengembangan kecerdasan emosional dan spiritual pengurus rayon di Pondok Modern Gontor - Saifulloh, Ahmad; Setiawan, Wahyu; Ahmad, Sutrisno; Huda, Muhammad Ilman Hafizhul; Raafi, Hafizh (Al-Liqo: Jurnal Pendidikan Islam, 2025)
This article examines the development of students’ emotional and spiritual intelligence through leadership education at Pondok Modern Darussalam Gontor. The pesantren implements a comprehensive educational approach that actively involves students in the learning process. Leadership education is carried out through the rayon management organization, entrusted to fifth-grade KMI students equivalent to eleventh-grade senior high school students. As rayon administrators, students assume continuous leadership responsibilities within a dynamic dormitory environment governed by a distinctive disciplinary system. Using a descriptive qualitative approach with participatory observation, in-depth interviews, and documentation, the study finds that direct leadership experience enhances emotional intelligence, including emotional regulation, empathy, communication, and conflict resolution. Spiritual intelligence also develops through routine religious practices and the internalization of Islamic values, strengthening students’ emotional–spiritual balance and leadership character.